Responding to Environmental Challenges in Alberta - Brown, Peter (Earth Common Journal, 2016)
Climate change and the myriad of challenges that come with it are a reality the entire world must face. However, for Canadian province, Alberta, the stakes are especially high. Oil and gas mining made up 18.3% of Alberta’s GDP in 2015 and therefore plays a significant role in its economy. Alberta has also been subject to degrading air quality and natural disasters like the recent Fort McMurray Fire. Provincial and municipal governments have, however, taken many steps to addressing the array of environmental challenges Alberta faces including releasing its Climate Leadership Report to Environment Minister Shannon Phillips, which outlines concrete goals and objectives. This paper discusses some of targets as well as legislation that have come out of the Climate Leadership Report. Furthermore, this paper explores how individuals have influenced the climate change discussion and how they can continue to spread environmental messages.